2012
DOI: 10.1007/s10886-012-0079-9
|View full text |Cite
|
Sign up to set email alerts
|

In the Nick of Time: Males of the Parasitoid Wasp Pimpla disparis Respond to Semiochemicals from Emerging Mates

Abstract: Males of the parasitoid wasp Pimpla disparis Viereck (Hymenoptera: Ichneumonidae) aggregate on parasitized gypsy moth, Lymantria dispar, host pupae when the emergence of a prospective mate is imminent or under way. We tested the hypotheses that the developing parasitoid ("DePa") inside the host pupal case produces a pheromone that attracts and arrests mate-seeking males, and that the pheromone is most effective during the emergence of the parasitoid from the host. Results obtained in two-choice laboratory expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Searching for emergence sites will be favored if females mate only once and are immediately receptive after emergence (Godfray 1994). In fact, male parasitoids are known to aggregate at female emergence sites (Matthews et al 1979, Hrabar et al 2012. Hrabar et al (2012) suggested that oral ßuids that soften the host cuticle during eclosion function as sex pheromones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Searching for emergence sites will be favored if females mate only once and are immediately receptive after emergence (Godfray 1994). In fact, male parasitoids are known to aggregate at female emergence sites (Matthews et al 1979, Hrabar et al 2012. Hrabar et al (2012) suggested that oral ßuids that soften the host cuticle during eclosion function as sex pheromones.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, male parasitoids are known to aggregate at female emergence sites (Matthews et al 1979, Hrabar et al 2012. Hrabar et al (2012) suggested that oral ßuids that soften the host cuticle during eclosion function as sex pheromones. Males of I. naranyae also search for female emergence sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and to arrest in response to a semiochemical cue associated with the emergence of a prospective mate from the host pupa (Hrabar et al., ). As emerging females do not engage in active long‐range signalling (Hrabar et al., ), the males' ability to time their presence at parasitized host pupae prior to or during emergence of a prospective mate is intriguing. A simple strategy for these males would be to stay for days on the same parasitized pupa, and to await the emergence of the prospective mate.…”
Section: Introductionmentioning
confidence: 99%
“…A simple strategy for these males would be to stay for days on the same parasitized pupa, and to await the emergence of the prospective mate. For P. disparis , waiting seems a risky strategy, considering that males would take a 50% chance that the prospective mate is indeed a female (Hrabar et al., ), and that they would miss other mating opportunities elsewhere. Alternatively, if males were capable of identifying and memorizing the location of many parasitized pupae, they could repeatedly visit them, track their development, and more likely be present at the time of parasitoid emergence.…”
Section: Introductionmentioning
confidence: 99%